Deposition of Graphene-like carbon on copper foil using Methane
Graphene, a two-dimensional carbon allotrope that is made up of single-layer sp2 hybridized carbon atoms arranged in a hexagonal configuration. Since graphene was discovered in year 2004, graphene research has surged exponentially owing to its unique and remarkable properties. A variety of methods have been proposed to synthesize graphene layer of which the most promising method is using chemical vapour deposition (CVD). However, there still lie a lot of issues about effects of reaction parameters and growth mechanism in the catalytic growth using CVD method. For example, is the separation of the graphene from the substrate and uniformity of graphene layer on the substrate. In this study, catalytic decomposition of methane was employed for producing graphene layer on copper foil. The reaction parameters in CVD process including reaction times, reaction temperatures and methane flow rates were varied to study the impact of these parameters on the graphene samples. Various characterization tests including Scanning Electron Microscopy (SEM), Energy Dispersive X-ray (EDX), X-ray diffraction (XRD), Raman spectroscopy and X-ray photoelectron spectroscopy (XPS) were carried out on the graphene samples produced. The agglomerations of carbon were observed at the grain boundaries of the copper substrate. The carbon content on the graphene sample increased when the reaction time, reaction temperature or methane flow rate were increased. This indicated that more and more carbon atoms were deposited on the copper foil when the reaction time, reaction temperature and methane flow rate were increased. On the other hand, the weight percentage of carbon agglomeration at the grain boundaries was higher than that of the centre of grains in all samples. Besides, XRD diffraction peak for the copper oxide and small graphite peak at 2θ=26.5° were seen which signified very low quantity of graphene-like carbon structures were formed under high reaction times (90 and 300 seconds), high reaction temperature (1050°C) and methane flow rates (200-600mlpm). In addition, XPS results confirmed the presence of the C1s spectrum at 284.8eV which ascribed to the existence of sp2-hybridized carbon on the samples. With this sp2-hybridized carbon, it is confirmed again very low amount of graphene-like carbon materials were synthesized and distributed randomly on the surface of our samples. However, no Raman peak at D(1350cm-1), G(1580cm-1) and 2D(2700cm- 1) were shown to represent the graphene on the sample but only the Raman peaks of copper oxide were detected. From above results, the produced samples contain very small amount of graphene layer due to two limitations: no hydrogen gas and high methane flow rate were used. Furthermore, the presence of oxygen species in the CVD furnace even further hinders the formation of graphene layer and eventually, the graphene layer was less likely to be formed on the copper substrate.